An Uncommon Cause of a Small-Bowel Obstruction - Zakaria, Ali (Case Rep Gastrointest Med, 2017)
Sarcoidosis is a systemic granulomatous disease of unknown etiology, characterized by the formation of noncaseating granulomas. Gastrointestinal (GI) system involvement that is clinically recognizable occurs in less than 0.9% of patients with sarcoidosis, with data revealing small intestine involvement in 0.03% of the cases. A high index of suspension is required in patients presenting with small-bowel obstruction and previous history of sarcoidosis. Establishing a definitive diagnosis of GI sarcoidosis depends on biopsy evidence of noncaseating granulomas, exclusion of other causes of granulomatous disease, and evidence of sarcoidosis in at least one other organ system. Treatment of GI sarcoidosis depends on symptomatology and disease activity. Herein, we are presenting a case of 67-year-old female patient who had acute small-bowel obstruction at the level of jejunum with postoperative histopathologic evidence of noncaseating granulomatous inflammation with multinucleated giant cells, consistent with sarcoidosis.